An alternative formula for the constant growth model - Forsyth, Juan A. (2019)
Purpose – The traditional one-stage constant growth formula has two main underlying assumptions: a company will be able to maintain its competitive advantage for completed investments in perpetuity and each year in the future it will be able to generate new investment opportunities with the same competitive advantage which will also remain in perpetuity. The purpose of this paper is to develop a model that limits the duration of the competitive advantage. Design/methodology/approach – A new model is developed and it is used to value a public company. Findings – In this study the author introduces an alternative formula considering the duration of the competitive advantage imposing a restriction on the fact that extraordinary returns cannot be sustained forever and also separates the part of the value explained by the current investments from the portion of value created by future investments. Originality/value – The traditional one-stage constant growth model used to determine the continuing value of a company has limitations regarding the duration of the competitive advantage. The developed formula corrects the problem limiting the time extraordinary returns will remain over time.